Nar-Dos in "Anahid" magazine and in Archag Tchobanian's evaluations - Avagyan, Vachagan (Bulletin of Yerevan University B: Philology, 2023)
Current article, focusing on Archag Tchobanian’s references on Nar-Dos and his work in different issues of "Anahid" magazine in 1930s, the aesthetic and public views of the famous literary critic on the work of the famous novelist are thoroughly presented for the first time. Although familiar with Nar-Dos's literature from a distance, through mediation, Tchobanian made subtle and interesting observations about the writer's worldview, artistic method and thinking system. The task of article’s author is to reveal the aesthetic standards of evaluation of Tchobanian the literary critic, pointing out both valuable observations and controversial, disputable or unacceptable thoughts and views.In the first part of the article, an extensive space is given to the famous art critic Aram Yeremyan’s interview with Nar-Dos, where the author's comments on his own life and work complete his portrait as a writer.
Keywords: Nar-Dos; Archag Tchobanian; cultural rapprochement; interview; biography; literary influence; artistic method; originator of the Armenian realist novel; public interest; orientation; revolution; worldview